2022
DOI: 10.1007/s12040-022-02005-w
|View full text |Cite
|
Sign up to set email alerts
|

Urban Heat Island vulnerability mapping using advanced GIS data and tools

Abstract: Urban Heat Island (UHI) is a phenomenon that can cause hotspots in city areas due to dense, impervious infrastructure and minimal vegetation cover. UHI hotspots may become worse in extreme heat events that are already aAecting many regions across the globe due to increased frequent hot extremes, humaninduced warming in cities, and rapidly growing urbanization, as documented by the latest IPCC report 2021. In seeking to support designers, planners, and decision-makers in developing and implementing adaptation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…84 The simultaneous effect of greater temperatures, limited access to cooling measure, and reduced green space cause residents in densely populated places more vulnerable to the negative impacts of UHI. 80 Health status The susceptibility of individuals to the effects of urban heat islands and elevated temperature is influenced by their health status. In this review we found that, those with chronic illnesses, disabilities, limited mobility, and taking specific medication, were particularly vulnerable to negative health effects in extreme temperatures.…”
Section: Household Incomementioning
confidence: 99%
“…84 The simultaneous effect of greater temperatures, limited access to cooling measure, and reduced green space cause residents in densely populated places more vulnerable to the negative impacts of UHI. 80 Health status The susceptibility of individuals to the effects of urban heat islands and elevated temperature is influenced by their health status. In this review we found that, those with chronic illnesses, disabilities, limited mobility, and taking specific medication, were particularly vulnerable to negative health effects in extreme temperatures.…”
Section: Household Incomementioning
confidence: 99%
“…Climate change and its induced disasters have become more frequent and severe during the past few decades, having severe ramifications for many sectors of countries around the world [ 1 , 2 ]. The changes, such as temperature fluctuations, rainfall variability, and shifts in the arrival of seasons, have triggered various risks, especially in sectors such as agriculture [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Urban Heat Vulnerability (HV) has been widely investigated in light of the urgency to adapt and mitigate climate change impacts on inhabitants and the built environment. An increasing number of methods -and associated indicators -based mostly on statistical data have been developed in recent years [1][2][3][4][5][6]. For these reasons, a relevant number of studies use the census-tract level for HV assessment, due to the need to find accessible data and calculate the demographic, socioeconomic and environmental indicators constraining the modelling [7].…”
Section: Introductionmentioning
confidence: 99%